(untitled) (International Journal of Natural Sciences, 2011)
This study was conducted to establish the normal dimensions of the different segments of the female reproductive tract of the Black Bengal goats. The reproductive tracts of 56 adult non-gravid, female Black Bengal goat were collected and biometric parameters of different segments of the female reproductive tracts i.e. vulva, vagina, cervix, uterine body, uterine horns, oviducts and ovaries were measured .The lengths of the right and left ovaries were 1.453±0.034 and 1.410±0.026 cm, respectively. Mean weight of left ovary was 0.5944±0.06 gm and that of right ovary was 0.614±0.07 gm in Black Bengal goat. The average numbers of follicle in right and left ovaries were 4.123±0.230 and 3.893±0.229, respectively. The mean lengths of the vulva, vagina, cervix, uterine body, uterine horns and oviduct were 2.671±0.063, 7.132±0.165, 3.348±0.113, 2.50±0.112 and 12.287±0.270 and 10.150±0.228 cm, respectively. The width of the vagina, cervix, uterine body and uterine horn were 3.972±0.098, 1.7551±0.042, 2.739±0.079 and 2.805±0.069 cm, respectively. The average number of curuncle in uterus was 54.714±1.70. A significant difference (p<0.05) between right and left ovaries was found for ovario-bursal adhesion. The mean weight, length and width in the present study were found higher in right ovaries than those of left ovaries. Key wards: Black Bengal goat; biometric parameters; ovary; uterus; cervix; vagina. DOI: http://dx.doi.org/10.3329/ijns.v1i1.8609 International Journal of Natural Sciences (2011), 1(1):12-16